Teacher Centered Vs Student Centered: Study of ‎Memorizing Qur’an (taḥfiẓ) at Integrated Islamic Elementary ‎School Al Anis Kartasura Suhoharjo - Musyafangah Musyafangah (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
The program of memorizing of Quran (taḥfiż) in Islamic Schools is the main attraction in the screening of new students, especially in the Integrated Islamic Elementary School (SDIT), one of them is Al Anis Kartasura Sukoharjo which has implemented it from 2006 to the present with the target of two part (in 29th and 30th of Quran) or 1263 verses plus the Yanbu’a program’s and Reading Qur’an 30 part by seeing. The focus of the research is to evaluate the Taḥfiż curriculum and its learning outcomes. The author collects datas by curriculum documents, interview several teachers and evaluate student learning outcomes. Finally the author finds that taḥfiż learning at Al-Anis used several methods begin from verse by verse, listening, writing, drilling and together, all methods, to improve the students abilities. In other, the teachers use teaching learning centers, because they judge its more appropriate than the student learning center because teaching of the Qur’an like teaching a foreign language.